Overcoming multidrug resistance by a combination of chemotherapy and photothermal therapy mediated by carbon nanohorns. Issue 36 (26th August 2016) - Wang, Junling; Wang, Ran; Zhang, Fangrong; Yin, Yajun; Mei, Leixia; Song, Fengjuan; Tao, Mingtao; Yue, Wanqing; Zhong, Wenying
Abstract : A targeted drug delivery system based on carbon nanohorns for targeting P-glycoprotein and delivering etoposide into cells to overcome multidrug resistance. Abstract : Multidrug resistance (MDR) is a major obstacle to cancer chemotherapy due to the overexpression of P-glycoprotein (P-gp). Herein, etoposide (ETO) was loaded onto oxidized carbon nanohorns (oxCNHs), which were modified by polyethylene glycol (PEG) and further functionalized with the targeting ligand P-gp monoclonal antibody (PA) in an attempt to overcome MDR. The obtained drug delivery system (ETO@oxCNHs/PEG-PA) showed high drug loading efficiency, enhanced drug release under laser irradiation, improved cellular uptake and increased therapeutic effect both in vitro and in vivo . In addition, NIR laser irradiation had a synergistic effect on overcoming MDR. The MDR-overcoming mechanism could be the efficient cellular uptake, enhanced drug release and reduced drug efflux by P-gp. These results demonstrated that ETO@oxCNHs/PEG-PA could be a promising drug delivery system for cancer MDR reversion.